Assessment of different approaches to public service provision by the City of Johannesburg Metropolitan Municipality - Kwangwane, Thulani Thompson (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPA (School of Public Management and Planning))--Stellenbosch University, 2008.